IN-VITRO CHARACTERIZATION OF SOMACLONAL VARIANT AGAINST SALT TOLERANCE BY ANALYSING ANTIOXIDATIVE DEFENCE SYSTEM AND SECONDARY TABOLITES INARTEMISIA ANNUA L - ANJANA KUMARI,; NEHA PANDEY,; RAM PRASAD MEENA DEEPIKA TRIPATHI,; SHASHI PANDEY-RAI, (International Journal of Pharma and Bio Sciences, 2016)
In the present study wild type and stable somaclonal variant (M3 lines) of Artemisia annua L. were subjected to different concentration of (NaCl) and monitored for their performance in terms of growth and biochemical parameters as well as artemisinin (antimalarial drug) biosynthesis. Somaclonal variant survived under higher concentrations of salt however wild type survived in a healthy way only upto 150 mM NaCl, suggesting somaclonal variants to be more tolerant to salinity as compared to wild type. Attestation to this inference was brought by various analyses such as generation of H2O2, activation of antioxidative defence enzymes such as SOD and CAT, proline accumulation, lipid peroxidation, level of Na+ and K+ and sugar level in both wild type and somaclonal variant of A. annua. These results suggest that activation of defence against salt stress is better in somaclonal variant than in wild type plants. Artemisinin was found to be higher in somaclonal variant as compared to control even in the absence of salt stress. Further, salt-stress-mediated induction in artemisinin level as well as expression of key biosynthetic genes was greater in somaclonal variant as compared to wild type. The results conclude that somaclonal variant of A. annua may be considered as stress tolerant candidate for future breeding and can be cultivated at commercial level to meet the ever increasing demand of artemisinin.